Django project blueprints : develop stunning web application projects with the Django framework - Ahmed, Asad Jibran (Community experience distilled., 2016)
Develop stunning web application projects with the Django framework About This Book Build six exciting projects and use them as a blueprint for your own work Extend Django's built-in models and forms to add common functionalities into your project, without reinventing the wheel Gain insights into the inner workings of Django to better leverage it Who This Book Is For If you are a Django web developer able to build basic web applications with the framework, then this book is for you. This book will help you gain a deeper understanding of the Django web framework by guiding you through the development of seven amazing web applications. What You Will Learn Create a blogging platform and allow users to share posts on different blogs Prioritise user-submitted content with an intelligent ranking algorithm based on multiple factors Create REST APIs to allow non-browser based usage of your web apps Customize the Django admin to quickly create a full-featured and rich content management system Use Elasticsearch with Django to create blazing fast e-commerce websites Translate your Django applications into multiple languages Dive deep into Django forms and how they work internally In Detail Django is a high-level web framework that eases the creation of complex, database-driven websites. It emphasizes on the reusability and pluggability of components, rapid development, and the principle of don't repeat yourself. It lets you build high-performing, elegant web applications quickly. There are several Django tutorials available online, which take as many shortcuts as possible, but leave you wondering how you can adapt them to your own needs. This guide takes the opposite approach by demonstrating how to work around common problems and client requests, without skipping the important details. If you have built a few Django projects and are on the lookout for a guide to get you past the basics and to solve modern development tasks, this is your book. Seven unique projects will take you through the development process from scratch, leaving no stone unturned. In the first two projects, you will learn everything from adding ranking and voting capabilities to your App to building a multiuser blog platform with a unique twist. The third project tackles APIs with Django and walks us through building a Nagios-inspired infrastructure monitoring system. And that is just the start! The other projects deal with customizing the Django admin to create a CMS for your client ...